The expansion and diversity of the CYP75 gene family in Vitaceae - Yang Xiao; Jun Wen; Ran Meng; Ying Meng; Qiang Zhou; Ze-Long Nie (PeerJ, 2021)
The CYP75 gene family plays an important role in flavonoid biosynthesis in plants. Little is known about the evolution of the gene family within the grape family. Here, we extracted the CYP75 genes from transcriptome data of 15 grape species and 36 representative genomes from other plants to explore the evolutionary history of the CYP75 gene family in Vitaceae. The structure of the CYP75 protein sequences is highly conserved with the variation mainly occurring in the N terminal and the middle region. The evolutionary analyses suggested classifying the CYP75 gene family into three groups in Vitaceae, namely Vitaceae A1, Vitaceae A2 and Vitaceae B. The Vitaceae A1 and A2 belong to the CYP75A subfamily and the Vitaceae B belongs to the CYP75B subfamily. Within the Vitaceae A1, most Vitaceae taxa present only one copy of the CYP75A protein sequence except for Vitis vinifera with a high number of sequences, which might have originated through recent gene duplications after its split from the other species. Vitaceae A2 contain only CYP75A sequences from Vitaceae sister to one from Camellia sinensis, probably representing a relict lineage. The CYP75B proteins were found to be dominated in Vitaceae and other angiosperms. Our results provide important insights into understanding the evolutionary history of the CYP75 gene family in Vitaceae and other angiosperms.